Social Responsibility Is A Tool To Encourage Investment In Renewable Energies And Achieve Sustainable Development In Algeria - A Reading Of Reality And Hope - بارك نعيمة; تقررت يزيد; معيوف هدى (My University, 2021)
This research paper aims to shed light on the need to achieve sustainable development and protect the environment through a systematic approach as part of the social responsibility program, because it is extremely important in encouraging investment in renewable energies as a direction to achieve sustainability, and this focuses on the most important measures taken by Algeria as a first step In the journey to encourage investment in renewable energies as an alternative to the rentier economy and towards the embodiment of sustainability